Appraisal of Comparative Therapeutic Potential of Undoped and Nitrogen-Doped Titanium Dioxide Nanoparticles - Ahmad, Muhammad Arslan (Molecules, 2019)
Nitrogen-doped and undoped titanium dioxide nanoparticles were successfully fabricated by simple chemical method and characterized using x-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive x-ray (EDX), and transmission electron microscopy (TEM) techniques. The reduction in crystalline size of TiO(2) nanoparticles (from 20–25 nm to 10–15 nm) was observed by TEM after doping with N. Antibacterial, antifungal, antioxidant, antidiabetic, protein kinase inhibition and cytotoxic properties were assessed in vitro to compare the therapeutic potential of both kinds of TiO(2) nanoparticles. All biological activities depicted significant enhancement as a result of addition of N as doping agent to TiO(2) nanoparticles. Klebsiella pneumoniae has been illuminated to be the most susceptible bacterial strain out of various Gram-positive and Gram-negative isolates of bacteria used in this study. Good fungicidal activity has been revealed against Aspergillus flavus. 38.2% of antidiabetic activity and 80% of cytotoxicity has been elucidated by N-doped TiO(2) nanoparticles towards alpha-amylase enzyme and Artemia salina (brine shrimps), respectively. Moreover, notable protein kinase inhibition against Streptomyces and antioxidant effect including reducing power and % inhibition of DPPH has been demonstrated. This investigation unveils the more effective nature of N-doped TiO(2) nanoparticles in comparison to undoped TiO(2) nanoparticles indicated by various biological tests. Hence, N-doped TiO(2) nanoparticles have more potential to be employed in biomedicine for the cure of numerous infections.